Analisis Korelasi Antara Kadar Sisa Klor dan pH Pada Air Bersih PDAM Surabaya - Aussie Amalia; Nara Naomi Aprilia Putri (Prosiding ESEC, 2023)
Clean water is river water that is managed by the Regional Drinking Water Company (PDAM) into water that meets predetermined regulations. According to the Regulation of the Minister of Health of the Republic of Indonesia Number 736/Menkes/PER/VI/2010 and the Regulation of the Minister of Health of the Republic of Indonesia Number 492/Menkes/PER/IV/2010, one of the parameters managed is to remove particles (pathogenic bacteria), remove residual chlorine levels and maintain the pH in the clean water. The purpose of this study is to analyze the correlation between residual chlorine and pH in clean water. This research is a study that uses data for 2 months in 2022, namely in August and September. The data was entered into Minitab 17 software with normality, correlation and simple linear regression test methods. The results obtained in this study are in August and September have almost the same results. The results in August have a very small correlation that can be said to have no correlation between residual chlorine and pH, while in September has a small correlation between residual chlorine and pH.